Features of pregnancy, childbirth and newborn pregnant teen in height. - Mejía, Eliseo (2015)
OBJECTIVES: To determine the factors that have contributed to pregnancies occur in adolescence, and the characteristics and risks of the same height in a population. DESIGN: Retrospective descriptive study of 423 medical records in Jauja-Junin (3375 m) between January and June 1996. RESULTS: The incidence of early pregnancies in adolescents (under 16 years) was 5.4% between late adolescence ( 16 to 19 years) and 21.3% among pregnant women aged 19 to 30 years 73.3%. increased incidence of celibacy, unemployment, abortion, preeclampsia, preterm delivery and low birth weight in pregnant adolescent early as in the late was found; and increased incidence of celibacy, unemployment, stillbirth, caesarean section, preeclampsia, eclampsia, preterm delivery, postpartum and neonatal abnormal pathology in pregnant women between 16 and 19 years than in the 19 to 30 years. He had no prenatal more than 80% of pregnant women in the three study groups. CONCLUSIONS: The incidence of maternal complications and newborn are higher in pregnant teen in pregnant women of 19-30 years of age. Also, these complications are more common at altitude than sea level.